Are there regional variations in the presentation of childhood leukemia? - Silva, Klerize de Souza; Rechenmacher, Ciliana; de Morais, Rahuany Velleda; Michalowski, Mariana Bohns; Daudt, Liane Esteves (Clinical and Biomedical Research, 2021)
Introduction: Treatment of childhood acute lymphoblastic leukemia (ALL) is based on risk stratification. This study aimed to assess the agreement between risk group classifications in the different childhood ALL treatment protocols used in a referral hospital in southern Brazil. Methods: We retrospectively reviewed the medical records of patients aged 1 to 18 years with B-cell ALL treated at a hospital from January 2013 to April 2017. Agreement between risk classifications was assessed by the kappa coefficient. Results: Seventy-five patients were analyzed. There was poor agreement between risk stratification by GBTLI 2009 and BFM 95 protocols (kappa=0.22; p = 0.003) and by GBTLI 2009 and IC-BFM 2002 protocols (kappa=0.24; p = 0.002). Risk group distribution was 13.3% for low risk, 32.0% for intermediate risk, and 54.7% for high risk based on stratification by the GBTLI 2009 protocol, and 28.0% for low risk, 42.7% for intermediate risk, and 29.3% for high risk based on stratification by the IC-BFM 2002 protocol. Overall survival was 68.6%. Conclusion: This study provides numerous points to ponder about the treatment of leukemia in Brazil. The percentage of patients classified as high risk in our sample was higher than that reported in the international literature. This difference, however, had no impact on overall survival, which was shorter than that reported in the international literature.